Physiochemical and Spectral Characterization For a Biological Active, Solanidine&Solasodine Partial Purification Compounds From (Solanum nigrum L) - Mohammed, A. S.; Fayidh, M. A.; Saooer, K. Y. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This study includes a physiochemical and a spectrocpical characterization to some alkaloid compounds in the (ANAB AL- THEAB) plant (Solanum nigrun L.). It’s the most important medicinal herb belonging to the family (Solanaceae). Acid hydrolysis was performed by using limited conc. of Hcl and H2SO4, to obtain the aglycon part of previously separated steroidal componants as (A, B and C). The characterization of the(A,B and C) compounds indicates that they varied between them as the separated steroidal like-alkaloids, carried by using melting point (m.p.), thin layer chromatography (TLC), Infra -Red spectroscopy (IR) and Ultra violet-Visible spectroscopy (UV - Visible).High performance liquid chromatography (HPLC) indicated the presence of single characteristic intense peak belonging to (A) component which confirms the purity of components. The Mass- spectra (MS) of this compound gave (397m/z) molecular weight peak related to (Solanidine) alkaloid, when the chararacteristic to compound (C) showed that same as solasodine alkaloid . .